The Role of E-Filing, Perceived Ease of Use, and Perceived Usefulness in Improving Corporate Taxpayer Compliance - Hidayanto, Dwi Kurnia; Aprilia, Shilvi; Nababan, Naomi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
This study aims to examine the effect of e-filing, perceived ease of use, and perceived usefulness on corporate taxpayer compliance, especially in Sukabumi, West Java. This study used a quantitative approach. The questionnaire distributed to 50 corporate taxpayers in Sukabumi who have used the e-filing tax service system. Analysis of the data was done using multiple linear regression. The results of the study showed that the use of e-filing, Perceived Ease of Use, and Perceived Usefulness had a positive effect on corporate taxpayer compliance.